Nanotechnology for Mitigating Impact of COVID-19 - Tripathi, Dr. Gagan Kant; Rathore, Harshit; Chavali, Murthy; Rathore, Deepshikha (Journal of Applied Science, Engineering, Technology, and Education, 2021)
This review article aims to create awareness towards COVID-19 epidemic and develop a basic responsibility in human beings to control and stop the transmission of COVID-19. It has been highlighted that disaster is imminent if we play with nanostructures unknowingly. The effect of COVID-19 on mankind and its detection and transmission have also been discussed briefly. The protection guidelines including treatment procedures have been illustrated. The utilization of nanoparticles to detect and cure COVID-19 has been described.